SOLUTION OF PRIVATE TASKS OF CYLINDRICAL SHEAR WAVES (in the case of the distribution of constant values γ-α + 2> 0 and α = β) - Seitmuratov, A.; Aitimov, M.Zh; Seitkhanova, A.; Ostayeva, A.; Tulegenova Е.; Janyssova, D.; Shamilov, T. (Academic Scientific Journal of Computer Science, 2020)
Many studies usually use two methods to determine wave characteristics. First-The instantaneous state of the medium corresponding to a certain fixed moment of time is investigated. Second-The change in time of the state of the body in question at some fixed point is investigated. If studies are carried out taking into account the rheological properties of the material of the system in question or, if there is an environment surrounding the system, which also generally exhibits rheological properties, the use of these methods is significantly difficult. In such cases, the influence of rheological parameters on the components of the complex phase velocity at certain values of the vibration frequencies is studied.